Factors Related To The Occurrence Of Typoid Fever At Sawah Lebar Health Center In Bengkulu City - Sri Wulandari; Yusran Fauzi; Fery Surahman (Journal of International Public Health, 2026)
Typhoid fever is a major health problem in both developed and developing countries. Indonesia, with its tropical climate, makes tropical diseases easily spread. The prevalence of typhoid fever is increasing, with 8.5 million people infected and 10.2 million people infected. In Indonesia, the prevalence of typhoid fever also increases annually. Data from 2022 recorded 736,000 typhoid fever patients in Indonesia. Data from 2023 recorded approximately 645,000 typhoid fever patients in Indonesia. Estimated data for 2024 indicate a trend of cases remaining high, at approximately 690,000 cases. This research is a quantitative study with a cross-sectional design. The sample used was accidental sampling over a one-week period. Data were analyzed using the Chi-square test. The results of the study showed that almost most of the respondents had a risky age, namely 52 people (53%%), most of the respondents had good knowledge, namely 35 people (36.1%), and most of the respondents had a history of typhoid fever, namely 45 people (46.4%) and almost all of the respondents had the habit of eating outside the home, namely 58 people (59.8%). There was a significant correlation in the age variable (p-value = 0.002 <α 0.05), there was a significant correlation in the Knowledge variable (p-value = 0.005 <α 0.05), there was a significant correlation in the typhoid fever history variable (p-value = 0.005 <α 0.05). There was no correlation between the variable of eating out habits (p-value = 1.000 < α 0.05). The health center is expected to coordinate more frequently with health authorities to monitor and improve surveys and provide education. The community is also expected to be actively involved in participating in typhoid fever prevention activities at Sawah Lebar Health Center.